Study of biofilm formation in Salmonella species isolated from food - Soltan Dallal, Mohammad Mehdi; Khalifeh-gholi, Mohammad; Rahmani, Hojjat; Sharifi-yazdi, Sara; Haghighat Khajavi, Shabnam; Sharifi Yazdi, Mohammad Kazem (The European Research Journal, 2019)
Objectives: Biofilms are defined as communities of organisms attached to a surface and producing an extracellular matrix, in which the bacteria are imbedded. Infections with Salmonella species represent a major health problem and a significant burden on food industry. Biofilm formation is one of the causes of pathogenicity of Salmonella species, especially in the food industry, which allows bacteria to bind to different levels. Many outbreaks have been associated with biofilms, because they quickly resist anti-microbial and cleansing agents. The aim of this research was to study the capability of biofilm formation by Salmonella species isolated from food. Methods: A total of 8 Salmonella species were isolated from 400 samples of red meat, chicken, eggs, and vegetables. Identification was carried out by conventional biochemical tests and serotyping. The capability of biofilm production was measured by titration in Crystal Violet microplate. Results: In the phenotypic study of Salmonella isolates with turbidity method at 550 nm without acetic acid, only 2 (25%) of isolates were able to produce biofilm. both of isolates belonged to the group D of Salmonella. Conclusions: The capability of the isolates to form biofilm reveals the potential ability to resist antimicrobial chemotherapy, therefore higher levels of hygiene in production, packaging, and supply are necessary.